Estimation of Cephalic index in 17-20 Years old population of Nimad region of Madhya Pradesh - Anil Mangeshkar; Ashok B Najan; Vineet Kumar Gohiya; Sarita Gohiya (Institute of Medico-legal Publications Pvt Ltd, 2021)
Identification is determination of the individuality of a person based on certain physical characteristics andis of importance in solving criminal as well as civil cases on a regular basis. Examination of fragmentaryremains by a doctor can aid the police in complete identification of an individual. Cephalic index is onesuch parameter that can help in identification of the individual. Cephalic index (CI) and head shape aregreatly affected by geographical, sex, age and racial factors. Such data is of great medico legal and forensicimportance which indicates that cephalic index can be used as marker of ethnicity. There have been variousinstances where the race of the individual bone has to be ascertained in solving issues related to forensicor archaeological importance where Cephalic index is an important tool to determining the race and sex ofan individual whose identity is unknown. This study was carried out to determine Cephalic index of 400healthy individual, including 200 Male and 200 Female individuals between 17 years to 20 years the of age,from the Nimad region of Madhya Pradesh.